Pelatihan Sulaman Tangan untuk Meningkatkan Kreativitas Perajin UMKM Binaan BUMN (Bank BRI) di Kota Padang Panjang - Asmidar Asmidar; Purwo Prihatin; Sumadi Sumadi; Heruningrum Heruningrum; Andra Saputra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The background of this activity is an effort to increase the creativity and production capacity of MSME artisans under the guidance of State-Owned Enterprises, especially Bank Rakyat Indonesia (BRI), in Padang Panjang City. MSME artisans in this area have great potential in developing local culture-based products, but still face limitations in design innovation, technical skills, and product diversification that are competitive in the market. This community service activity aims to increase the creativity, technical skills, and production capacity of artisans through hand embroidery training. The implementation team carried out the activity to 20 MSME artisans under the guidance of BRI in Padang Panjang City. The methods used in this activity were lecture and direct practice. The lecture method provided an understanding of the types of materials, tools, basic to advanced techniques, and the development of embroidery designs based on traditional and contemporary motifs. Meanwhile, the practice method was carried out through intensive mentoring so that participants were able to master embroidery skills in an applicable manner. The results of this activity showed that participants succeeded in producing various innovative products, including hand-embroidered headscarves, as well as fashion accessories based on embroidered fabrics with a wider variety of decorative motifs. Participants demonstrated improved skills, demonstrated by their ability to combine colors, independently develop motifs, and enhance the neatness and quality of their embroidery techniques. This activity had a positive impact in terms of improving product quality, fostering artisan creativity, and strengthening the economic independence of MSMEs in Padang Panjang City. Indicators of success were seen in the improvement in participants' technical skills, product diversification, and artisan readiness to develop value-added products for a wider market.